2008
DOI: 10.1111/j.1937-8327.1991.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Information, Instruction, and Learning: A Hypermedia Perspective

Abstract: Hypermedia as defined by Osgood (1987) is a tool for linking nonlinear information presented in the form of graphics, animation, video, and sound. One important question for instructional designers regarding hypermedia is how it can be used as an instructional or learning tool that enhances rather than inhibits learning. Creating hypermedia applications is a quick and easy alternative to creating courseware with older authoring systems and languages which took many hours to learn. This ease of application crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In addition, action learning (Dean, 1998;Marquardt, 1998), a hypermedia approach (Grabowski & Curtis, 1991), organizational learning (Proctor & Gubler, 2001), and instructional systems design and HPT models (Ertmer & Newby, 1993;Joo, 1998;Schwen et al, 2006) were still influential topics in HPT. Figure 7).…”
Section: Cohesive Subgroups In the Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, action learning (Dean, 1998;Marquardt, 1998), a hypermedia approach (Grabowski & Curtis, 1991), organizational learning (Proctor & Gubler, 2001), and instructional systems design and HPT models (Ertmer & Newby, 1993;Joo, 1998;Schwen et al, 2006) were still influential topics in HPT. Figure 7).…”
Section: Cohesive Subgroups In the Networkmentioning
confidence: 99%
“…Figure 6 shows that Schwen et al (2006) was the central player, creating connections with nine articles. Grabowski and Curtis (1991) was a source of faction 4 through links to Joo (1998) and Ertmer and Newby (1993). Schwen's contribution to this faction was noticeable in terms of authoring 6 of 10 articles.…”
Section: Cohesive Subgroups In the Networkmentioning
confidence: 99%
“…(2) a short description of the LMS feature; (3) a classification of the LMS feature with regard to the three design elements information, instruction, and learning (see Grabowski and Curtis 1991); (4) the LMS feature's association with instructional functions (see Hilgenstock and Jirmann 2005); and (5) exemplary recommendations for instructional use.…”
Section: Taxonomy Of Lms Featuresmentioning
confidence: 99%
“…Table 5.3 shows the taxonomy, which contains (1) the name of the LMS feature; (2) a short description of the LMS feature; (3) a classification of the LMS feature with regard to the three design elements information, instruction, and learning (see Grabowski and Curtis 1991); (4) the LMS feature's association with instructional functions (see Hilgenstock and Jirmann 2005); and (5) exemplary recommendations for instructional use. Using the results of the pairwise comparisons and the confidence ratings, the authors identified specific LMS features that are applicable for designated instructional functions.…”
Section: Designing Effective Online Instruction Within An Lmsmentioning
confidence: 99%
“…As a result of increases in the incorporation of hypermedia into the learning environment, it is essential to address both the beneficial and constraining factors associated with this educational tool (Grabowski & Small, 1997).…”
Section: Hypermediamentioning
confidence: 99%